PENGARUH KEGIATAN EKSTRAKULIKULER TERHADAP PEMBENTUKAN KARAKTER SISWA SMA - Landeva Kharisma; Didit Darmawan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Increasingly complex social changes require education to be oriented not only toward academic achievement but also toward character development. One effort Schools can make to support character education is through extracurricular activities that provide social learning experiences and direct value instillation. This study aims to analyze the influence of extracurricular activities on character development in high school students through a literature review of various published quantitative studies. The research method used was a literature review of ten quantitative research articles relevant to the research topic. Data analysis was conducted descriptively and qualitatively to comprehensively illustrate the relationship between the two variables. The results of the study indicate that student involvement in extracurricular activities has a positive relationship with character development, particularly in aspects of discipline, responsibility, cooperation, leadership, and religious character. Religious extracurricular activities tend to contribute more to strengthening religious character, while non-religious activities such as Scouting play a greater role in developing students' social and personal character. Overall, the effectiveness of extracurricular activities in character development is influenced by the intensity of student involvement, the consistency of program implementation, and the support of the school environment and culture. Therefore, extracurricular activities need to be managed in a planned and sustainable manner as a strategic part of implementing character education at the high school level.